Use of Jargon in Literature - Mekhribon Rasulqizi Sadullayeva (Periodica Journal, 2022)
This research work touches on a rather important topic: jargon, their development and use by people in colloquial and written speech. In this work, the student well revealed her goals: Defined what jargon is; I traced the history of jargon, their changes over time; I found out how the jargons of different groups and strata of society differ from each other; Identified the main group of jargon.
Keywords: Literature; socio-historical experience; social-group; Dictionary